Behavior of novel hybrid lightweight concrete composites under drop-weight impact loading. (December 2021) - Batran, Tayseer Z.; Ismail, Mohamed K.; Hassan, Assem A.A.
Abstract: This investigation evaluated the feasibility of combining lightweight concrete (LWC) and engineered cementitious composite (ECC) in specific configurations to develop a lightweight hybrid composite with improved impact resistance. In this study, three mixtures were investigated: one LWC mixture fully produced with lightweight fine and coarse expanded slate aggregates; one ECC mixture developed with polyvinyl alcohol fibers (ECCP); and one ECC mixture developed with steel fibers (ECCS). For testing, cylindrical specimens and small-scale beams were constructed in a two-layer composite system having different configurations (i.e., different arrangements and depths). Additional specimens fully cast with LWC, ECCP, and ECCS were tested for comparison. The interface bond strength between LWC and either ECCP or ECCS was also evaluated. The performance of the developed composites was assessed under static flexural loading and drop-weight impact. The results showed that both ECCP and ECCS could achieve a good bonding with LWC substrate, i.e., above 90% of that measured for the monolithic LWC specimens, even with no surface preparations (i.e., roughening or using shear keys). Combining LWC with either ECCP or ECCS generated novel lightweight hybrid composites that can offer superior performance for different structural lightweight members exposed to high impact loading. For given arrangement and depth, the LWC-ECCS composite exhibited higher mechanical and impact performance whereas the LWC-ECCP was distinguished by achieving an excellent impact resistance at a lighter self-weight.